Efficient cache replacement policy for minimising error rate in L2-STT-MRAM caches. (2018) - Olanrewaju, Rashidah F.; Khan, Burhan Ul Islam; Khan, Abdul Raouf; Yaacob, Mashkuri; Alam, Md. Moktarul
The current research statistics for cache designing reveals that Spin Torque Transfer Magnetic RAMs (STT-MRAMs) have become one of the most promising technologies in the field of memory chip design, gaining a lot of attention from researchers due to its dynamic direct map and data access policies for reducing the average cost i.e. both time and energy optimisation. In this paper, the vulnerability of STT-MRAM caches has been investigated to examine the effect of workloads as well as process variations for characterising the reliability of STT-MRAM cache. The current study is intended to analyse and evaluate an existing efficient cache replacement policy namely Least Error Rate (LER) which utilises Hamming Distance (HD) computations to reduce the Write Error Rate (WER) of L2-STT-MRAM caches with acceptable overheads. The performance analysis of the algorithm ensures its effectiveness in reducing the WER and cost overheads as compared to the conventional LRU techniques.